Ameloblastin Upregulates Inflammatory Response Through Induction of IL‐1β in Human Macrophages. Issue 10 (3rd May 2017) - Otsuka, Mai; Okinaga, Toshinori; Ariyoshi, Wataru; Kitamura, Chiaki; Nishihara, Tatsuji
ABSTRACT: Ameloblastin (AMBN) is an enamel matrix protein that has various biological functions such as healing dental pulp and repairing bone fractures. In the present study, we clarified the effect of AMBN on the expression of an inflammatory cytokine, interleukin‐1β (IL‐1β) in lipopolysaccharide (LPS)‐treated human macrophages. Real‐time RT‐PCR analysis showed that LPS treatment upregulated expression of the IL‐1β gene in U937 cells. Interestingly, AMBN significantly enhanced IL‐1β gene expression in LPS‐treated U937 cells as well as the secretion of mature IL‐1β into culture supernatants by these cells. AMBN also activated caspase‐1 p10 expression in LPS‐treated U937 cells. Pretreatment with a caspase‐1 inhibitor, Z‐YVAD‐FMK, downregulated the mature IL‐1β expression enhanced by AMBN treatment in LPS‐treated U937 cells. A co‐immunoprecipitation assay showed that treatment with LPS and AMBN upregulated toll‐like receptor 4 (TLR4) and myeloid differentiation primary response gene 88 (MyD88) interactions, but there was no significant difference compared with LPS treatment alone in U937 cells. In contrast, western blot analysis revealed that AMBN remarkably prolonged the phosphorylation of extracellular signal‐regulated kinase 1/2 (ERK1/2), a member of the mitogen‐activated protein kinase (MAPK) family. An ERK1/2‐selective inhibitor, U0126, suppressed expression of the IL‐1β gene as well as its protein expression in U937 cells treated with LPS and AMBN. Taken together, these results indicate that AMBN enhances IL‐1β production in LPS‐treated U937 cells through ERK1/2 phosphorylation and caspase‐1 activation, suggesting that AMBN upregulates the inflammatory response in human macrophages and plays an important role in innate immunity. J. Cell. Biochem. 118: 3308–3317, 2017. © 2017 Wiley Periodicals, Inc. Abstract : (1) We clarified the effect of AMBN on the expression of an inflammatory cytokine, IL‐1β in LPS‐treated human monocyte cell line U937 cells. (2) AMBN significantly induced the secretion of IL‐1β in LPS‐treated U937 cells. (3) AMBN remarkably prolonged the phosphorylation of ERK1/2 in LPS‐treated U937 cells.